2012
DOI: 10.1002/jms.3105
|View full text |Cite
|
Sign up to set email alerts
|

Collision‐induced dissociation study of poly(2‐ethyl‐2‐oxazoline) using survival yields and breakdown curves

Abstract: Poly(2-ethyl-2-oxazoline), a synthetic polymer was analysed by mass spectrometry using different ion sources. Two distributions could be identified in the mass spectra which related to two different polymer series (one with hydrogen and hydroxyl end-groups and the other with methyl and hydroxyl end-groups). The fragmentation behaviour of the protonated oligomers was studied in a quadrupole time-of-flight mass spectrometer (MS) with electrospray, atmospheric pressure chemical ionization and direct analysis in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…It has been demonstrated that Energy‐Resolved CID tandem Mass Spectrometry (CID ERMS) and the Survival Yield (SY) representation may allow unequivocal structural and quantitative analysis of a compound despite the presence of iso‐meric/baric interferences 5–11 . SY curves of pure compounds are indeed usually sigmoidal.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that Energy‐Resolved CID tandem Mass Spectrometry (CID ERMS) and the Survival Yield (SY) representation may allow unequivocal structural and quantitative analysis of a compound despite the presence of iso‐meric/baric interferences 5–11 . SY curves of pure compounds are indeed usually sigmoidal.…”
Section: Introductionmentioning
confidence: 99%
“…Under such conditions, the precursor ions generally undergo multiple collisions before enough internal energy has been accumulated to enable dissociation. E LAB may be varied in steps to acquire MS/MS spectra as a function of internal energy and derive breakdown graphs and survival yield (SY) curves, which reveal information about the dissociation energetics and stability of the precursor ion relative to the product ion fragments (Biri et al, 2012; Wesdemiotis, 2017).…”
Section: Structural Characterization Via Tandem Mass Spectrometry (Ms...mentioning
confidence: 99%
“…This behavior has its origins in the ejection dynamics which depend on the 3D structure. As already discussed in literature, when the 3D structure changes, the ejection dynamics change [48] (DP [22][23][24][25][26][27][28][29][30][31][32], leading to the correlation between the observed MS/ MS and IM-MS behaviors.…”
Section: Crossing Ms/ms and Im-ms Informationmentioning
confidence: 99%
“…The increasing compositional and architectural complexity of PAOx and other synthetic polymers developed for advanced applications is giving rise to analytical challenges as the conventional techniques fall short of providing a complete description of the polymer structure (e.g., co-monomer sequence, polymer topologies and branching, isomer identification). PAOx have been the subject of a number of in-depth analytical studies involving mass spectrometry, shedding light on fragmentation pathways [23][24][25], polymerization mechanism [26,27], and unveiling chain transfer reactions [28,29] or the mechanisms associated with polymer degradation [30].…”
Section: Introductionmentioning
confidence: 99%